Flavour science : recent advances and trends - Bredie, Wender L. P.; Petersen, Mikael Agerlin (Developments in food science ;, 2006)
The flavor of a food is often the most desirable quality characteristic for the consumer, yet the understanding of flavour is a fascinatingly complicated subject, which calls for interdisciplinary research efforts. This latest volume presents the proceedings of the 11th Weurman Flavour Research Symposium and describes the most recent and original research advances related to the flavour of foods and beverages with contributions of experts from 25 countries world-wide. * Efficiently summarises the current front line research within food flavor * Highlights the modern approaches to flavor production using biotechnology, enzymes and gene-technology * The dynamic effects of manipulation of food in the mouth during consumption influencing the release of flavour compounds is discussed in detail.